2004
DOI: 10.1126/science.1090908
|View full text |Cite
|
Sign up to set email alerts
|

Guar Seed ß-Mannan Synthase Is a Member of the Cellulose Synthase Super Gene Family

Abstract: Genes for the enzymes that make plant cell wall hemicellulosic polysaccharides remain to be identified. We report here the isolation of a complementary DNA (cDNA) clone encoding one such enzyme, mannan synthase (ManS), that makes the beta-1, 4-mannan backbone of galactomannan, a hemicellulosic storage polysaccharide in guar seed endosperm walls. The soybean somatic embryos expressing ManS cDNA contained high levels of ManS activities that localized to Golgi. Phylogenetically, ManS is closest to group A of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
305
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(318 citation statements)
references
References 23 publications
8
305
0
2
Order By: Relevance
“…We have examined the monosaccharide composition of the endosperm over the course of development, applied the recently generated xyloglucan antibody to early endosperm development, and modified our approach to studying arabino-(1→4)-b-D-xylan using the LM11 antibody. Previous studies identifying genes involved in the synthesis of cell wall polysaccharides have shown that transcript accumulation correlates with the time of polysaccharide synthesis and deposition (Pear et al, 1996;Doblin et al, 2001;Dhugga et al, 2004;Brown et al, 2005;Persson et al, 2005;Cocuron et al, 2007;Mitchell et al, 2007). By coupling our immuno-EM observations with transcript profiles of candidate cell wall synthesis genes, we can now infer which subfamily members of these gene families is functional during key stages of endosperm development.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We have examined the monosaccharide composition of the endosperm over the course of development, applied the recently generated xyloglucan antibody to early endosperm development, and modified our approach to studying arabino-(1→4)-b-D-xylan using the LM11 antibody. Previous studies identifying genes involved in the synthesis of cell wall polysaccharides have shown that transcript accumulation correlates with the time of polysaccharide synthesis and deposition (Pear et al, 1996;Doblin et al, 2001;Dhugga et al, 2004;Brown et al, 2005;Persson et al, 2005;Cocuron et al, 2007;Mitchell et al, 2007). By coupling our immuno-EM observations with transcript profiles of candidate cell wall synthesis genes, we can now infer which subfamily members of these gene families is functional during key stages of endosperm development.…”
Section: Discussionmentioning
confidence: 86%
“…For example, there is ample evidence associating the GLUCAN SYNTHASE-LIKE (GSL) gene family with callose [(1→3)-b-D-glucan] biosynthesis (Brownfield et al, 2009). Heterologous expression experiments coupled with gene expression profiles have implicated the CslC gene family in the synthesis of the glucan backbone of xyloglucan (Cocuron et al, 2007) and cellulose (Dwivany et al, 2009) whereas members of the CslA gene family have been shown to have mannan or (gluco)mannan synthase activity (Dhugga et al, 2004).…”
Section: Polysaccharides [In Particular (1→3 1→4)-b-d-glucan and Aramentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence similarity of the CSL genes to the CESA genes originally suggested that they also encode processive glycosyl transferases (Cutler and Somerville 1997). Recently, Dhugga et al (2004) showed that a CSL gene from guar encodes a b-1,4-mannan synthase. Thus, it seems likely that other CSL genes catalyze synthesis of various cell wall polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly few Csl genes have been assigned a specific function in plant cell wall biosynthesis. Members of the CslA subfamily encode (1,4)-b-D-mannan synthases (Dhugga et al, 2004;Liepman et al, 2007), and the CslC group is believed to encode an enzyme that directs the synthesis of the (1,4)-b-D-glucan backbone of xyloglucans (Cocuron et al, 2007). Using a comparative genomics approach, Burton et al (2006) showed that a cluster of the monocot-specific CslF genes in rice is located in a genomic region corresponding to one containing a major quantitative trait locus (QTL) for grain (1,3;1,4)-b-D-glucan content in barley (Hordeum vulgare).…”
mentioning
confidence: 99%